2011
DOI: 10.1152/jn.00936.2010
|View full text |Cite
|
Sign up to set email alerts
|

Diminished capacity to modulate motor activation patterns according to task contributes to thumb deficits following stroke

Abstract: Triandafilou KM, Fischer HC, Towles JD, Kamper DG, Rymer WZ. Diminished capacity to modulate motor activation patterns according to task contributes to thumb deficits following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…A recent study assessed the maximum thumb-tip forces of stroke survivors with severe or moderate hand impairment and in age-matched subjects with no neurological deficits [6]. The maximum active isometric thumb-tip forces that could be produced were recorded for each of 6 intended directions: distal, proximal, adduction, abduction, flexion, extension.…”
Section: Design Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study assessed the maximum thumb-tip forces of stroke survivors with severe or moderate hand impairment and in age-matched subjects with no neurological deficits [6]. The maximum active isometric thumb-tip forces that could be produced were recorded for each of 6 intended directions: distal, proximal, adduction, abduction, flexion, extension.…”
Section: Design Requirementsmentioning
confidence: 99%
“…Compared to the other digits, the thumb also has disproportionately large cortical representation, both in motor cortex [2] and sensory cortex [3], thereby contributing to its superior precision of proprioception [4] and independence of movement [5]. The thumb can also generate the strongest forces of any of the digits [6]. Not surprisingly, the thumb is involved in more than 50% of hand functions [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of mechanisms contribute to varying degrees to the diminished motor control, such as contracture 1 , muscle atrophy 2,3 , spasticity 4 , and excessive coactivation 5 , weakness plays a fundamental role 6 . This weakness is especially noticeable in the hand where isometric force generation can be reduced by 80% or more 7,8 . We have observed that force deficits during isokinetic movements are even greater 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Even after stroke survivors regain the ability to open their hands, functionality may remain limited due to a variety of impairments affecting task performance. For example, diminished capacity to voluntarily modulate muscle activities [15,16] or abnormal interactions between hand flexors and proximal muscles [17] can result in abnormal hand kinematics and kinetics, which may further lead to reduced workspaces [18], abnormal joint coordination [19], and misguided force at the thumb tip [15] and fingertip(s) [20]. Even if rigorous training could be performed with the help of skilled therapists, it would be labor-intensive and expensive, imposing a significant economic burden on patients.…”
Section: Introductionmentioning
confidence: 99%